An automatic procedure for deriving building portfolios using the Italian "CARTIS" online database. (December 2021) - Basaglia, A.; Cianchino, G.; Cocco, G.; Rapone, D.; Terrenzi, M.; Spacone, E.; Brando, G.
Abstract: Modelling of exposure is one of the most relevant challenges in seismic vulnerability assessments at the large scale, because of the large number of buildings to be handled whose geometrical and structural features may vary significantly. In these cases, it is convenient to identify a suite of archetype buildings that are deemed representative of the whole building stock. To this end, a novel procedure to define building portfolios for seismic vulnerability assessments at the regional/national scale is proposed. Building information is derived from an existing database for Italian municipalities that includes the main features of unreinforced masonry and reinforced concrete residential buildings surveyed with the so-called CARTIS form. The procedure is implemented in MATLAB to make the process of analysing the information for each municipality and identifying a manageable number of representative building sub-typologies fully automated and requiring only little input from the user. To show the potentialities of the procedure, it is applied to the Abruzzo Region, Central Italy.